2015
DOI: 10.1007/s00223-015-0001-x
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship of Bone Mineral Density to Oxidant/Antioxidant Status and Inflammatory and Bone Turnover Markers in a Multicenter Cross-Sectional Study of Young Men with Ankylosing Spondylitis

Abstract: Low bone mineral density (BMD) is an important complication of ankylosing spondylitis (AS) that seriously affects men and their quality of life, even in young patients. However, the relationships among redox; levels of bone turnover markers (BTMs), inflammatory markers and disease activity; and low BMD in AS require clarification. We recruited 102 men aged 30-39 year with AS and 102 healthy, sex- and age-matched controls for this cross-sectional study. The subjects were analyzed for lumbar spine and femoral ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 42 publications
0
22
0
Order By: Relevance
“…In SSc, serum-derived oxidative stress facilitates MSCs senescence 20 . Previously, we discovered an imbalance between oxidant biomarker and antioxidant levels in AS serum, which implied that disordered redox may participate in AS 5 . In this study, we found that AOPPs levels in AS serum were strongly and positively correlated with the extent of SA-β-gal staining and the expression of cell cycle arrest-related proteins in MSCs cultured with AS serum.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In SSc, serum-derived oxidative stress facilitates MSCs senescence 20 . Previously, we discovered an imbalance between oxidant biomarker and antioxidant levels in AS serum, which implied that disordered redox may participate in AS 5 . In this study, we found that AOPPs levels in AS serum were strongly and positively correlated with the extent of SA-β-gal staining and the expression of cell cycle arrest-related proteins in MSCs cultured with AS serum.…”
Section: Discussionmentioning
confidence: 99%
“…Alone with the chronic inflammation, AS patients always maintain a morbid serum microenvironment, which has been reported to be abnormal in terms of inflammatory factor and oxidative stress levels 3,4 . Previously, we also found that the levels of advanced oxidative protein products (AOPPs), a marker of oxidative stress, were elevated in AS and positively correlated with disease activity 5 . However, whether and how the AS serum microenvironment participates in AS pathogenesis are still unknown.…”
Section: Introductionmentioning
confidence: 86%
“…Wang et al have investigated bone markers, bone mineral density, and oxidation status in the AS patients. They found increased inflammatory markers, bone destruction products, and oxidation products in patients with active disease and suggested that oxidative stress plays an important role in the pathogenesis of AS and also influences bone mineral density [28].…”
Section: Discussionmentioning
confidence: 99%
“…Overall (I 2 = 87.4%, p = 0.000) Subtotal (I 2 = 90.1%, p = 0.001) = 96.8%, p = 0.000) Subtotal (I 2 = 91.7%, p = 0.000) Subtotal (I 2 = 95.2%, p = 0.000) Subtotal (I 2 = 87.0%, p = 0.000) Subtotal (I 2 = 94.5%, p = 0.000) Subtotal (I 2 = 90.9%, p = 0.000) Subtotal (I 2 = 95.2%, p = 0.000) Subtotal (I 2 = 92.7%, p = 0.000) Subtotal (I 2 = 99.1%, p = 0.000) Subtotal (I 2 = 90.0%, p = 0.002) Overall (I 2 = 94.4%, p = 0.000) Note: weights are from random effects analysis According to the scores of the Bath Ankylosing Spondylitis Disease Activity Index (BASDAI) used for patients and the visual analogue scale (VAS) used for physician, and the levels of CRP and ESR, AS patients can be divided into two groups: active patients with severe symptoms and inactive patients with mild symptoms. In this study, six articles evaluated the oxidative and/or antioxidative stress markers in AS patients with different disease activity [3,5,8,19,23,30]. The result of meta-analysis showed that the level of MDA and AOPP was higher in active patients, indicating a close relationship between oxidative injury products and the disease activity of AS.…”
Section: Discussionmentioning
confidence: 95%
“…Four studies [8,9,25,33] measured the oxidative and (or) antioxidative biomarkers in serum and erythrocytes and the others in serum only. Six studies [3,5,8,19,23,30] were included to analyze the association between oxidative stress and disease activity because they evaluated oxidative stress markers in patients with different disease activity. All studies ascertained patients using the modified New York criteria except two studies [4,34].…”
Section: Resultsmentioning
confidence: 99%